Dislocation dynamics simulation of Frank-Read sources in anisotropic alpha-Fe - Fitzgerald, S; Aubry, S; Dudarev, S; Cai, W (2012)
Frank-Read sources are among the most important examples of dislocation sources in crystals, and their operation facilitates dislocation multiplication and hence yield and plastic flow. Iron is known to become highly elastically anisotropic as the αγ transition at 912°C is approached, a temperature regime of critical importance for emerging technologies such as fusion and next-generation fission power generation. Using dislocation dynamics simulations based on anisotropic linear elasticity theory, we show that the isotropic elastic approximation leads to large errors in the activation stress of Frank-Read sources in iron at high temperatures. The critical stresses obtained from anisotropic elasticity are very different from the isotropic calculations and vary significantly between orientations. In particular, the increased variation of the dislocation energy with orientation leads to certain source configurations becoming operational at very low applied stresses, a result which is incompatible with isotropic elasticity, and is consistent with the very low yield stresses observed experimentally in α-Fe at high temperatures. © 2012 IOP Publishing Ltd.